2018
DOI: 10.1093/jac/dky147
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characterization of azole-resistant Aspergillus fumigatus in patients with cystic fibrosis: a prospective multicentre study in Germany

Abstract: This is the first multicentre study analysing the prevalence of ARAF isolates in German CF patients. Because of a resistance rate of up to 9%, susceptibility testing of A. fumigatus isolates from CF patients receiving antifungal treatment should be part of standard diagnostic work-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 28 publications
4
30
0
1
Order By: Relevance
“…We report the presence of TR 46 /Y121F/T289A now also from Iran, where until now only TR 34 /L98H had been isolated . This mutation, conferring voriconazole resistance, has been reported from both environmental (China, Taiwan, United Kingdom, Colombia, France, Germany, India, the Netherlands and Tanzania) and clinical sources (Spain, United Kingdom, France, Portugal, Argentina, Taiwan, Germany, China, Japan, United States, Denmark, Belgium and the Netherlands) (Table 1). All previous studies conducted in Iran for monitoring the mechanism of resistance among azole‐resistant A fumigatus in both clinical and environmental samples showed that the TR 34 /L98H mutation was reported with increasing frequency from 3.3% in 2013 to 6.6% in 2016 .…”
Section: Discussionmentioning
confidence: 73%
“…We report the presence of TR 46 /Y121F/T289A now also from Iran, where until now only TR 34 /L98H had been isolated . This mutation, conferring voriconazole resistance, has been reported from both environmental (China, Taiwan, United Kingdom, Colombia, France, Germany, India, the Netherlands and Tanzania) and clinical sources (Spain, United Kingdom, France, Portugal, Argentina, Taiwan, Germany, China, Japan, United States, Denmark, Belgium and the Netherlands) (Table 1). All previous studies conducted in Iran for monitoring the mechanism of resistance among azole‐resistant A fumigatus in both clinical and environmental samples showed that the TR 34 /L98H mutation was reported with increasing frequency from 3.3% in 2013 to 6.6% in 2016 .…”
Section: Discussionmentioning
confidence: 73%
“…Until now, few studies have evaluated azole‐resistant A. fumigatus in CF patients, whose prevalence varied greatly between centres and countries, and in all cases were <10% 14,15,22‐24 …”
Section: Discussionmentioning
confidence: 99%
“…Only limited data are available regarding the prevalence of azole‐resistant A. fumigatus isolates in CF subjects. The two largest studies investigating azole‐resistant A. fumigatus in CF patients were from the Netherlands 14 and Germany 15 . The Dutch multicentre study reported that 7.1% of A. fumigatus isolates were azole‐resistant with TR34/L98H (80%) being the dominating resistance mechanism followed by TR46/T289A/Y121F (16.4%), M220 (1.8%) and G54W (1.8%) 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All C. bertholletiae isolates were further tested using broth microdilution according to the EUCAST 9.3 standard as described elsewhere . Susceptibility was assessed for amphotericin B, itraconazole, voriconazole, caspofungin (Sigma‐Aldrich Life Sciences, Taufkirchen, Germany), posaconazole, micafungin, anidulafungin (mcePharma, Bilovec, Tschechien) and isavuconazole (Basilea Pharmaceutica, Basel, Switzerland).…”
Section: Methodsmentioning
confidence: 99%